Application of capillary electrophoresis for determination of taurine, choline, pantothenic acid, ascorbic acid and niacin to control the quality of dietary supplements - Nguyen, Thanh Đam; Nguyen, Manh Huy; Vu, Minh Tuan; Duong, Hong Anh; Pham, Hung Viet (Old Journal, 2018)
This study presented the application of capillary electrophoresis (CE) for determination of taurine, choline, pantothenic acid (vitamin B5), ascorbic acid (vitamin C) and niacin (vitamin B3) in dietary supplements. The range of the calibration curves were 2.0 ÷ 50 mg/L, and the linearities were good (R2 ≥ 0.997). The methods had good accuracy with high recoveries (89.3 ÷ 98.0% with deionized water and 94.7% ÷ 108.7% with real samples) and the differences of less than 10% in reference analysis for taurine by high performance liquid chromatography (HPLC). Analytical results showed that the concentrations of taurine in most samples were consistent with the label (